2020
DOI: 10.48550/arxiv.2010.05465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COGS: A Compositional Generalization Challenge Based on Semantic Interpretation

Abstract: Natural language is characterized by compositionality: the meaning of a complex expression is constructed from the meanings of its constituent parts. To facilitate the evaluation of the compositional abilities of language processing architectures, we introduce COGS, a semantic parsing dataset based on a fragment of English. The evaluation portion of COGS contains multiple systematic gaps that can only be addressed by compositional generalization; these include new combinations of familiar syntactic structures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
(14 reference statements)
0
21
0
Order By: Relevance
“…The main contributions of this paper are: (1) A study of the Transformer architecture design space, showing which design choices result in an inductive learning bias that leads to compositional generalization across a variety of tasks. (2) state-of-the-art results in some of the datasets used, such as COGS, where we report a classification accuracy of 0.784 using an intermediate representation based on sequence tagging (compared to 0.35 for the best previously reported model (Kim and Linzen, 2020)), and the productivity and systematicity splits of PCFG (Hupkes et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The main contributions of this paper are: (1) A study of the Transformer architecture design space, showing which design choices result in an inductive learning bias that leads to compositional generalization across a variety of tasks. (2) state-of-the-art results in some of the datasets used, such as COGS, where we report a classification accuracy of 0.784 using an intermediate representation based on sequence tagging (compared to 0.35 for the best previously reported model (Kim and Linzen, 2020)), and the productivity and systematicity splits of PCFG (Hupkes et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
“…Examples in the structural generalization tasks are typically longer than in the training set and require productivity. All the models tested in the original COGS paper (Kim and Linzen, 2020) (and all of our seq2seq approaches above) achieved 0 accuracy in this category, while performance on lexical tasks is mixed. The small-6s seq2seq model improves the overall performance from 0.278 to 0.475, but curiously has near 0 performance on Verb Argument Structure Alternation tasks, worse than the base abs seq2seq model.…”
Section: Intermediate Representation For Cogsmentioning
confidence: 95%
See 1 more Smart Citation
“…We show that pre-trained convolutions are competitive against pre-trained Transformers via a set of experiments on a potpourri of NLP tasks, like toxicity detection, sentiment classification, news classification, query understanding and semantic parsing/compositional generalization (Kim and Linzen, 2020). Moreover, we find that pretrained convolutions can outperform, in terms of model quality and training speed, state-of-the-art pre-trained Transformers (Raffel et al, 2019) in certain scenarios.…”
Section: Introductionmentioning
confidence: 86%
“…learning system (Chomsky, 2009;Lake, 2014;Lake et al, 2019). However, a range of curated datasets have revealed that standard deep neural networks struggle to generalize compositionally to novel utterances not seen during training (Shridhar et al, 2020;Kim & Linzen, 2020;Lake & Baroni, 2018).…”
Section: Introductionmentioning
confidence: 99%